Առաքելական ինքնագիտակցության վերագտնումը Ի. դարում - Անաստասիոս Յանուլատո (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Данная статья повествует нам о повторном приобретении апостольского самосознания людьми в 21 веке. Чтобы полноценно показать апостольское основание Вселенной единой Церкви, автор статьи сперва “возвращает” читателя в апостольские времена, приведя множество цитат из Нового Завета, тем самым указывая на то, что Церковь была основана Иисусом Христом и укреплена усилиями Его апостолов. This article is about the regain of human apostolic consciousness in the 21th century. To show the Church’s apostolic foundation, the author first of all refers to the period of the Apostles by numerous citations from the New Gospel, then states that the church was founded by Jesus Christ. Later, Lord’s body-the Church was strengthened due to the Apostles activity.
Keywords: Biography; Auxiliary Sciences of History; Christianity; Doctrinal Theology